Modeling Information Diffusion in Online Social Networks Using a Modified Firefly Algorithm - Alloush, Amjad; Rebdawi, Ghaida; Abou Trab, Mohammad Saeed (Journal of Information and Organizational Sciences, 2024)
The dynamics and patterns of information propagation on online social networks are complex and challenging to model and to predict. This study proposes a novel algorithm for simulating the spread of information on online social networks using a swarm-based approach. The algorithm is based on the firefly algorithm, which incorporates a new term called Vantablack to represent the non-spreader nodes in the network. The proposed algorithm is validated on three real-world datasets extracted from Kaggle.com, covering different topics and domains. The proposed algorithm outperforms other baseline methods in terms of accuracy and efficiency in predicting information diffusion.